Success and Impact of the 2024 European Universities Games on the University of Miskolc - Rakaczki, Zoltán (Theory, Methodology, Practice – Review of Business and Management, 2024)
The University of Miskolc implemented one of the most significant and complex projects in its history by hosting the 2024 European Universities Games. In the research, which is partly descriptive and partly empirical, I examine the success and impact of the event from the perspective of the University of Miskolc, utilizing management theory and sports science approaches. To provide a better understanding of the research question, I introduce the process of organizing the event. The changes in the legislative environment and organizational model of the hosted international sports events in Hungary have significantly affected the event’s project organization and, consequently, its execution. I will also look at another factor that influenced the large-scale project, the transformation of the University of Miskolc into a private university, similar to the co-organizer University of Debrecen. I participated in all phases of the organization of the event, I use primary data during the research.